The integration of telecommunication and dissemination networks. (5th April 2010) - Al-Mogren, Ahmad S.
Dissemination techniques may be used to enable users to get the needed data efficiently. In this paper, we describe an architecture which is designed to provide a flexible access to data in a multichannel dissemination-based network. The architecture is suitable to fit into the overall telecommunication network. An analytical study for the space and time overhead is presented to show the consistency of the system model.